Glycosaminoglycans Content and Type II Collagen Localization in Chondrogenic Differentiation of Adipose-Derived Mesenchymal Stem Cells Induced by L-Ascorbic Acid 2-Phosphate - Anggraini Barlian; Ni Luh Wisma Eka Yanti (Journal of Mathematical and Fundamental Sciences, 2020)
L-ascorbic acid 2-phosphate (LAA) is known to induce chondrocyte differentiation. The objective of this study was to analyze the potency of LAA in chondrogenic differentiation of adipose-derived mesenchymal stem cells (ADSC) by analyzing the glycosaminoglycans (GAG) content and type II collagen (Coll2) localization. ADSC was characterized using flow cytometry and cultured in media containing various concentrations of LAA (0, 25, 50, 100 Î¼g/mL) for 2, 3 and 4 weeks. Coll2 localization was analyzed by immunocytochemistry (ICC) using a confocal microscope. The quantification of GAG was performed by Alcian Blue staining and calcium deposition by Alizarin Red S staining. The results showed that ADSC was positive for mesenchymal stem cell (MSC) markers. Coll2 was localized in the cytoplasm and showed increasing abundance along with the increase of the LAA concentration. The highest intensity of Coll2 localization was shown in LAA 100 Î¼g/mL. ADSC in LAA induction medium showed higher GAG content compared to the control group (LAA 0 Î¼g/mL) (p < 0.05). The highest calcium deposit was shown by LAA 25 Î¼g/mL after 4 weeks of culture (p < 0.05) and it decreased at higher concentrations. In conclusion, LAA 100 Î¼g/mL is considered the optimum LAA concentration for chondrogenic differentiation.